Reproducing Human Arm Motion Using a Kinematically Coupled Humanoid Shoulder–Elbow Complex - M. M. Stanišić; C. M. Goehler (Applied Bionics and Biomechanics)
A challenge that is gaining interest in robotics is the development of humanoids, which are robots that assume an anthropomorphic form. A difficulty with humanoid design is the kinematic interpretation of human joints and the development of mechanisms that can mimic human motion. The focus of this work is the development of a kinematic description of the shoulder–elbow complex. A mechanism capable of reproducing voluntary human reaching motions is introduced along with the procedural method of implementing the coupled motions that exist within the human shoulder complex and shoulder–elbow complex. Experimental results are presented highlighting the accuracy of this mechanism along with the similarities to human configurations.